THE LIFE AND CAREER OF JOHANN SEBASTIAN BACH - Rahmonova Hojibuvi Rizojon qizi; Sanokul Dustov (Scholar Express Journal, 2022)
The article deals with the work of Johann Sebastian Bach, the content, direction, characteristics of his music, as well as the impact of the events of that period on Bach's music
Keywords: Aristocrats; polyphony; composer; organ